THE EFFECT OF STORYTELLING METHOD WITH POP UP BOOK MEDIA ON LISTENING SKILLS IN CHILDREN AGED 5-6 YEARS AT TKIT SYEIKH ABDURRAUF BANDA ACEH - helnita; Isdiyana; Wahidah Nasution (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Based on the background of the problem, the researcher found that the skills of group B1 children in listening have not developed optimally, this can be seen in the learning activities that have been carried out in listening using the storytelling method. The formulation of the problem in this study is whether the storytelling method formed by pop up book media affects listening skills in children aged 5-6 years. The study aims to determine whether the storytelling method formed by pop up book media has an effect on listening skills in children aged 5-6 years. The place of this research was conducted at TKIT Syeikh Abdurrauf Banda Aceh. This research is a quantitative study using the PreExperimental Designs approach. With the One-group prettest-posttest Design model. The data collection methods in this study were tests and documentation. The population in this study were all kindergarten B children and the sample of this study was group B1 consisting of 8 girls and 7 boys. The results of the research that has been done show that the calculation of the pre-test results obtained is still below the average value of 28.4 and the results of the post-test research calculation have a value above the average value of 81.4. Then Ho is rejected Ha is accepted or the data is normally distributed. So it can be concluded that the storytelling method formed by pop up book media affects listening skills in children aged 5-6 years at TKIT Syeikh Abdurrauf Banda Aceh.